2009
DOI: 10.1007/s00125-008-1255-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress is induced by islet amyloid formation and time-dependently mediates amyloid-induced beta cell apoptosis

Abstract: Aims/hypothesis Islet amyloid in type 2 diabetes contributes to loss of beta cell mass and function. Since islets are susceptible to oxidative stress-induced toxicity, we sought to determine whether islet amyloid formation is associated with induction of oxidative stress. Methods Human islet amyloid polypeptide transgenic and non-transgenic mouse islets were cultured for 48 or 144 h with or without the antioxidant N-acetyl-L-cysteine (NAC) or the amyloid inhibitor Congo Red. Amyloid deposition, reactive oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
193
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(207 citation statements)
references
References 46 publications
9
193
0
2
Order By: Relevance
“…It is, however, not clear which of these mechanism(s) contribute to hIAPP-induced beta cell death in primary islets, in which the level of endogenously produced hIAPP (pmol/l) is several fold lower [4,29] than that used in vitro (μmol/l). Recent studies using transgenic rodents have demonstrated that endoplasmic reticulum (ER) stress caused by formation of intracellular hIAPP fibrils [30,31] and oxidative stress [32] also contribute to cytotoxic effects of hIAPP. It therefore appears that, at least in vitro, hIAPPinduced beta cell apoptosis involves different mechanisms, although these mechanisms may share the same apoptotic signalling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…It is, however, not clear which of these mechanism(s) contribute to hIAPP-induced beta cell death in primary islets, in which the level of endogenously produced hIAPP (pmol/l) is several fold lower [4,29] than that used in vitro (μmol/l). Recent studies using transgenic rodents have demonstrated that endoplasmic reticulum (ER) stress caused by formation of intracellular hIAPP fibrils [30,31] and oxidative stress [32] also contribute to cytotoxic effects of hIAPP. It therefore appears that, at least in vitro, hIAPPinduced beta cell apoptosis involves different mechanisms, although these mechanisms may share the same apoptotic signalling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Of the two risk factors, evidence is accumulating that β-cell dysfunction, and the consequent inability to maintain appropriately elevated insulin secretion in the face of insulin resistance, is likely the more important factor precipitating the development of T2DM. 1 Several physiologic stressors have been proposed to explain the cause of this β-cell impairment, including glucolipotoxicity, 2 cytokines released from adipocytes and activated macrophages, 3,4 and islet amyloid deposition 5,6 among others (reviewed in ref. 7).…”
Section: β-Cell Dysfunction In Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…heparan sulphate proteoglycans) [24]; inducing endoplasmic reticulum stress [25] and oxidative stress [26]; and disruption of the endoplasmic reticulum-associated degradation (ERAD)/ubiquitin/proteasome system [27] and autophagy/ lysosomal pathway [28]. Although several mechanisms, at least in vitro, are involved in hIAPP-induced beta cell apoptosis, some of these may share the same apoptotic signalling pathways.…”
Section: Introductionmentioning
confidence: 99%